In Vitro Astroglial Dysfunction Induced by Neurotoxins: Mimicking Astrocytic Metabolic Alterations of Alzheimer’s Disease - Jéssica Taday; Fernanda Telles Fróes; Marina Seady; Carlos Alberto Gonçalves; Marina Concli Leite (Metabolites, 2024)
Astrocytes play fundamental roles in the maintenance of brain homeostasis. The dysfunction of these cells is widely associated with brain disorders, which are often characterized by variations in the astrocyte protein markers GFAP and S100B, in addition to alterations in some of its metabolic functions. To understand the role of astrocytes in neurodegeneration mechanisms, we induced some of these metabolic alterations, such as energy metabolism, using methylglyoxal (MG) or fluorocitrate (FC); and neuroinflammation, using lipopolysaccharide (LPS) and streptozotocin (STZ), which is used for inducing Alzheimer’s disease (AD) in animal models. We showed that MG, LPS, STZ and FC similarly caused astrocyte dysfunction by increasing GFAP and reducing S100B secretion. In the context of AD, STZ caused an amyloid metabolism impairment verified by increases in Aβ1-40 peptide content and decreases in the amyloid degradation enzymes, IDE and NEP. Our data contribute to the understanding of the role of astrocytes in brain injury mechanisms and suggest that STZ is suitable for use in vitro models for studying the role of astrocytes in AD.